Forging Samian ware in the Pannonian way: the case of stamped pottery - Nagy, Alexandra (Rei Cretariae Romanae Fautorum Acta, 2015)
The term pannonische Glanztonware is commonly used to describe either a variety of pottery with stamped decoration or ’plain’ ware with grey slip. These vessels were produced at an unknown number of sites in Pannonia but can be divided into three main types: Eastern, Western and South Pannonian. This study focuses on some groups found at Aquincum (one of the East Pannonian workshops) because more than 3000 stamped sherds have been identified here and tens of thousands of pieces of ‘plain grey ware’ as well. Based on this ceramic assemblage, some general conclusions can be drawn from the method, forms, decorative schemes and the motifs used in their manufacture.